Evaluating Android OS for embedded real-time systems - Maia, Cláudio (2014)
Since its official public release, Android has captured the interest from companies, developers and the general audience. From that time up to now, this software platform has been constantly improved either in terms of features or supported hardware and, at the same time, extended to new types of devices different from the originally intended mobile ones. However, there is a feature that has not been explored yet - its real-time capabilities. This paper intends to explore this gap and provide a basis for discussion on the suitability of Android in order to be used in Open Real-Time environments. By analysing the software platform, with the main focus on the virtual machine and its underlying operating system environments, we are able to point out its current limitations and, therefore, provide a hint on different perspectives of directions in order to make Android suitable for these environments. It is our position that Android may provide a suitable architecture for real-time embedded systems, but the real-time community should address its limitations in a joint effort at all of the platform layers.